BACTERIAL PATTERNS AND URINE CULTURE SENSITIVITY DESCRIPTION OF UROLOGY PATIENTS IN THE PAEDIATRIC POPULATION AT TERTIARY HOSPITAL - Permata, Veryne Ayu; Renaldo, Johan; Vermasari, Naritha (Indonesian Journal of Urology, 2025)
Objective: The aim of this research is to determine trends in urine culture and antibiotic resistance in pediatric urology patients in Soetomo General Hospital, January 2021-December 2023. Material & Methods: Medical record data and the microbiology laboratory database were studied retrospectively using a descriptive method. Identification of the pattern of antibiotic sensitivity for bacterial infection is the objective of the present study. Results: The most frequent bacteria cultured from 1,234 urine samples were: Escherichia coli 45%, Klebsiella pneumoniae 25%, and Pseudomonas aeruginosa 15%. E. coli exhibited high sensitivity to Meropenem (95%), Imipenem (93%), and Amikacin (90%), but strong resistance to Ampicillin (75%), Trimethopral-Sulfamethoxazole (70%), and Ciprofloxacin (65%). K. pneumoniae also displayed comparable resistance patterns. pneumoniae and P. aeruginosa, whose resistance to several drugs over the research period was clearly increasing. Conclusion: In summary, for juvenile uropathogens carbapenems and amikacin are still quite powerful therapeutic choices. These results highlight the critical requirement of responsible antibiotic use and continuous antimicrobial resistance surveillance in order to counteract increasing resistance trends and protect efficient treatment possibilities for children. Keywords: Urinary Tract Infections, Pediatric urology, Antibiotic resistance, Uropathogens, Escherichia coli